2018
DOI: 10.1039/c8cp04254c
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gaussianity, population heterogeneity, and transient superdiffusion in the spreading dynamics of amoeboid cells

Abstract: What is the underlying diffusion process governing the spreading dynamics and search strategies employed by amoeboid cells? Based on the statistical analysis of experimental single-cell tracking data of the two-dimensional motion of the Dictyostelium discoideum amoeboid cells, we quantify their diffusive behaviour based on a number of standard and complementary statistical indicators. We compute the ensemble- and time-averaged mean-squared displacements (MSDs) of the diffusing amoebae cells and observe a prono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 220 publications
7
76
0
Order By: Relevance
“…, as usual Q = F k k -for simplicity we may neglect the fluctuations counted in the next interval after the trapping events. Directly from (27) we see that S 2 has a geometric distribution. Any such variable can be expressed as an integer part of some exponentially distributed variable, E say, and therefore it has values between E and E−1.…”
Section: Short Memory Random Coefficient Ar(1)mentioning
confidence: 88%
See 3 more Smart Citations
“…, as usual Q = F k k -for simplicity we may neglect the fluctuations counted in the next interval after the trapping events. Directly from (27) we see that S 2 has a geometric distribution. Any such variable can be expressed as an integer part of some exponentially distributed variable, E say, and therefore it has values between E and E−1.…”
Section: Short Memory Random Coefficient Ar(1)mentioning
confidence: 88%
“…Note that for fixed k the pair Φ k , Θ k may, and generally will be dependent. Averaging (27) yields…”
Section: Short Memory Random Coefficient Ar(1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have interestingly revealed anomalous diffusion or deviations from purely Brownian motion (1526) thus making studies of probe particles in many biophysical systems an active area of research. Examples of systems where anomalous diffusion occurs include entangled F-Actin networks (1719), living cells (20, 21), cytoplasm (22, 23), colloidal liquids (24, 25), and lipid membranes (26), among others. Anomalous diffusion, is often characterized analytically using fractional Brownian motion (fBm), which follows power law scaling of the form (13, 15), < Δ x 2 ( τ ) > ~ τ α .…”
Section: Introductionmentioning
confidence: 99%